Development of Inquiry-Based Natural Science Learning Modules on Classification Materials and Their Changes for Class VII Junior High School/MTs - Widya Rahmi Harefa; Dalifati Ziliwu; Agnes Renostini Harefa (CV. Rayyan Dwi Bharata, 2023)
The problems in this study are educators who have not used the science learning module in the teaching and learning process and the low learning outcomes of students because of the lack of students' ability to construct the knowledge they get. The aims of this study were: to know feasibility, to know practicality, to know the effectiveness of inquiry-based learning modules in material classification materials and their changes for class VII SMP/MTs in the learning process. This research is a development research using the 4D development model which consists of define, design, develop, disseminate. The instrument used is a validation questionnaire which includes aspects of content feasibility, language feasibility, and design feasibility, student response questionnaires and learning achievement tests. The feasibility of inquiry-based modules by lecturers as content and material expert validators obtained a score of 85 with a 100% achievement level in the